Emergency Department Nurses’ Clinical Competence and Its Related Factors: A cross-sectional study - Fatemeh Jalalian; Seyed Mohammad Hosseininejad; Seyed Hossein Montazer; Ali Hesamzadeh (Asia Pacific Journal of Health Management, 2023)
Objectives: This study aimed to assess perceived clinical competence levels of emergency department nurses in Iran and to identify association with the demographic variables.